The Effect of Pyramidal Ownership Structure to the Financing Policies and Firm Value in Indonesia: Cronyman as Moderating Variable - Hety Budiyanti; Suad Husnan; Mamduh Hanafi (Jurnal Dinamika Akuntansi)
The research to examine the effects of ownership structures on financing policies and firm valuation. The populations are all listed companies in Indonesia Stock Exchange for period of 2013 and 2015. The sample selection technique used purposive sampling and resulting in a final sample of 72 listed firms. Empirical tests are conducted using multiple regressions and two stages least squares regression to test the simultaneous relationship between ownership structure, financing policies and firm value. The estimated results provide support for the hypotheses proposed that the separation of cash flow rights and control rights have led the use of excess leverage among pyramidal companies to preserve ultimate owner’s control. However, we failed to find a significant relationship between firm’s leverage and firm’s value. The conclusion is the simultaneounity relation between ownership structure, leverage and firm value appear that only the ownership structure significantly related with leverage and firm value. Also firm value and leverage ownership impact the ownership structure. Meanwhile, leverage does not appear to have a significant relation with the firm value, or the other way around.